Good-Bye Lenin (or Not?): The Effect of Communism on People's Preferences - Alesina, Alberto; Fuchs-Schündeln, Nicola (American Economic Review, 2007)
Preferences for redistribution, as well as the generosity of welfare states, differ significantly across countries. This paper tests whether there exists a feedback process of the economic regime on individual preferences. We exploit the experiment of German separation and reunification to establish exogeneity of the economic system. We find that, after German reunification, East Germans are more in favor of state intervention than West Germans. This effect is especially strong for older cohorts. We further find that East Germans' preferences converge toward those of West Germans. It will take one to two generations for preferences to converge completely. (JEL D12, D72, H11, H23, P26)